"Banana chocolate chips" D'Banana Enterprise / Mohd Nor Adnie Abd Gani ... [et al.] - Abd Gani, Mohd Nor Adnie; Jimin, Jessieca Audrine; Julianus, Clayrina; M. Aneh, Veronica; Minsuan, Jemmytie (2009)
Presently, we can see that many businesses operated here and there in Malaysia especially Sabah itself. Some of them were very successful and some of them were not very good in their business. All of these depends on the entrepreneur itself whether they can manage and control their businesses properly or not. Usually, the main purpose of entrepreneurs open a business is to get maximum profit. After considering of the economic circumstances and services that exist in Kota Kinabalu, Sabah, our group choose to involve in a food service industries. We named our business as D' Banana Enterprise. We involve in the activity of producing and selling banana chips coated with chocolate products at Kota Kinabalu as at present, the people especially the teenagers likes to eat a chip. This obviously shows that it can create good opportunity to gain profit and indirectly contribute to the economic development of our country. We also have come to a conclusion to set-up our D' Banana Enterprise at Kg Kituau Penampang. In our point of view, the target markets in our business are teenagers and kids around Kota Kinabalu. Other than that, our target market is also the resident of Kota Kinabalu and other working people because our product are made to make their life easy. Based on our survey, we do have competitors but their business is operating individually and .all of them did not use a chocolate. We will be the first entrepreneur to open a premise that sells a banana chips coated with chocolate of products under the name of D' Banana Enterprise in Kota Kinabalu. So, we believe that we can challenge our competitors based on our advantages. In conclusion, our group will survives for a number of years or even more because of our product is the one and only in Kota Kinabalu and we believe that our product will have a bright future.